2013
DOI: 10.2522/ptj.20130109
|View full text |Cite
|
Sign up to set email alerts
|

Participation Following Knee Replacement: The MOST Cohort Study

Abstract: Although there was a mean increase in participation ≥1 year following TKR, participation restriction was common. The likelihood of low participation was increased among women, non-whites, and those with depressive symptoms, severe pain in either knee, or worse pre-TKR function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…2012, Maxwell et al. 2013) have found statistically significant improvements after surgery. A study that used the SF-36 found no effect on social function; however, the dropout level from that study was substantial (63% at 2 years after surgery) (Xie et al.…”
Section: Discussionmentioning
confidence: 96%
“…2012, Maxwell et al. 2013) have found statistically significant improvements after surgery. A study that used the SF-36 found no effect on social function; however, the dropout level from that study was substantial (63% at 2 years after surgery) (Xie et al.…”
Section: Discussionmentioning
confidence: 96%
“…Current qualitative research has not addressed this question explicitly 38e40 and existing quantitative research has focused on frequency or quantifying amount of activity without addressing socio-cultural factors that impact why people do and do not return to activity 10e13 . For example, Maxwell et al identified that individuals under 65 years had decreased limitations in participation measured by the Late Life Disability Index 41 whereas those 75 years and older had increased restrictions 1 year following total knee replacement 42 . These authors additionally identified that depressive symptoms, lower pre-surgery function and other knee symptoms were associated with more participation limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that 30% of patients with TKA still have participation restriction 1 year after the surgery (Maxwell et al, 2013). Recent evidence suggests that 30% of patients with TKA still have participation restriction 1 year after the surgery (Maxwell et al, 2013).…”
Section: Participation Restriction Measuresmentioning
confidence: 99%
“…The disability component of the late life function and disability instrument (LLFDI) can be used to quantify participation restrictions in patients with TKA (Maxwell et al, 2013). Patients are asked to rate the extent of the limitation (limitation domain) that they feel in performing 16 life tasks and the frequency of performing these tasks (frequency domain).…”
Section: Late Life Function and Disability Instrumentmentioning
confidence: 99%